"You have no voice!": Constructing reputation through contemporaries in the Shakespeare biopic - Kirwan, Peter (Johns Hopkins University Press, 2014)
This article addresses the construction of Shakespearean reputation and legacy in contemporary film through re-evaluation of the much-derided Anonymous (Roland Emmerich, 2011), in addition to John Madden's Shakespeare in Love (1998). In both films, the framing, presentation and performance of Shakespeare's contemporaries (Jonson, Marlowe, Nashe, Dekker and Webster) is key to an understanding of how both films figure what it means to be "Shakespeare" and what it means to be "not-Shakespeare". Viewing Shakespeare and his work through the eyes of his fellow writers, the films position Shakespearean reputation as formed both by and in spite of the observations of his friends and rivals.